Dual-targeted nanomedicines for enhanced tumor treatment. (February 2018) - Zhu, Yaqin; Feijen, Jan; Zhong, Zhiyuan
Graphical abstract: Highlights: Different types of dual-ligand nanomedicines for tumor-targeted imaging and therapy. Advantages of dual-ligand nanomedicines in tumor-targeting. Factors that affect the targeting efficacy of dual-ligand nanomedicines. The role of cell penetrating peptides in combination with targeting ligands. Approaches for improved design and evaluation of the effect of dual-ligand nanomedicines. Abstract: Based on the overexpression of specific receptors on tumor cells, active targeting nanomedicines have been developed with the ability to efficiently deliver imaging agents in the tumor area or anticancer drugs into tumor cells via receptor-mediated endocytosis. Nevertheless, the efficacy of single-ligand nanomedicines is still limited due to the complexity of the tumor microenvironment. In recent years, dual-ligand nanomedicines have attracted a lot of interest, because these nanomedicines endowed with versatile functions, have the potential to improve the efficacy of tumor-targeted delivery. In this review, an overview of various dual-ligand nanomedicines for tumor targeted therapy will be presented, the role of cell penetrating peptides in combination with targeting ligands will be discussed and factors that affect the targeting efficacy of dual-ligand nanomedicines will be evaluated.